Steroid metabolome profiling of follicular fluid in normo- and hyperandrogenic women with polycystic ovary syndrome. Issue 206 (February 2021) - Yang, Zuwei; Zhou, Wenzhong; Zhou, Chengliang; Zhou, Yuzhong; Liu, Xinmei; Ding, Guolian; Hu, Yulian; Pan, Jiexue; Sheng, Jianzhong; Jin, Li; Huang, Hefeng
Highlights: NA-PCOS and HA-PCOS had statistically similar steroid metabolome map in FF. HA-PCOS and NA-PCOS had a generally decreased steroidogenesis in FF than controls. Follicular androgen levels in NA-PCOS and HA-PCOS were similar but higher than in controls. No much correlation between follicular steroid levels and baseline characteristics. Abstract: Polycystic ovary syndrome (PCOS) is a heterogeneous disease defined by the presence of at least two of the following features: hyperandrogenism, oligoanovulation (OA), and polycystic ovarian morphology (PCOM). Hyperandrogenism is considered the cornerstone of PCOS. However, the most prevalent phenotype in Chinese women with PCOS is OA + PCOM [normo-androgenic PCOS (NA-PCOS)]. It has been reported that PCOS women have higher androgen levels in follicular fluid (FF), but whether NA-PCOS women have the same intrafollicular steroid profiles as hyperandrogenic PCOS (HA-PCOS) women has not been explored. In this study, we analyzed 17 steroids in stimulated size-matched ovarian follicles (16−18 mm) from 166 controls and 141 PCOS women [87 NA-PCOS and 54 HA-PCOS women, defined by a single serum testosterone (T) immunoassay measurement] using liquid chromatography tandem mass spectrometry, and investigated their relationship with baseline characteristics. No significant differences in intrafollicular steroid levels and product/precursor ratios between NA-PCOS and HA-PCOS women were observed, though HA-PCOS women had significantly higher serum luteinizing hormone and T levels than NA-PCOS women. NA-PCOS and HA-PCOS women had significantly higher levels of androstenedione (AD), T and free androgen index, higher enzyme activity of P450c17 (AD/17OH-progesterone), 3βHSD2 (17OH-progesterone /17OH-pregnenolone) and P450c11 (corticosterone /11-deoxycorticosterone), lower levels of pregnenolone, 17OH-pregnenolone and 11-deoxycorticosterone, and decreased enzyme activity of P450aro (estrone/AD and estradiol/T) and 5α-reductase (dihydrotestosterone/T) in FF than controls. NA-PCOS women had significantly higher intrafollicular cortisol levels and lower 11βHSD2 (cortisone/cortisol) activity than controls. Baseline serum T levels were slightly correlated with intrafollicular estrogens (E1: r = 0.192, p = 0.019; E2: r = 0.248, p = 0.002; E3: r = 0.248, p = 0.002) and androgens (DHEAS: r = 0.276, p = 0.001; AD: r = 0.185, p = 0.032; T: r = 0.173, p = 0.044) in controls and PCOS women respectively. Serum anti-Müllerian hormone (AMH) levels and antral follicle count (AFC) were correlated with intrafollicular cortisol (AMH: r = 0.380, p = 0.000; AFC: r = 0.177, p = 0.036) and corticosterone (AMH: r = 0.212, p = 0.048; AFC: r = 0.219, p = 0.009) levels in PCOS women. In conclusion, NA-PCOS and HA-PCOS women had statistically similar steroid metabolome profiles in FF, both of which showed a generally decreased steroidogenesis and hyperandrogenism compared to controls.